1996
DOI: 10.1159/000189334
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Accumulation of Uremic Toxins in the Blood and Their Precursors in the Feces after Oral Administration of Lebenin®, a Lactic Acid Bacteria Preparation, to Uremic Patients Undergoing Hemodialysis

Abstract: The plasma levels of phenol, p-cresol, and indican are markedly increased in uremic patients, and cannot be efficiently reduced by hemodialysis. Such uremic toxins, which are produced in the intestine as bacterial putrefactive metabolites, accumulate to a great degree in the feces of hemodialysis patients. Oral administration of Lebenin®, a preparation consisting of antibiotic-resistant lactic acid bacteria, reduced the levels of fecal putrefactive metabolites to levels comparable with those of healthy subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
217
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(241 citation statements)
references
References 12 publications
16
217
2
6
Order By: Relevance
“…The same authors also demonstrated that oligo-fructose-inulin significantly reduced p-cresyl sulfate generation rates and serum concentrations in hemodialysis patients (Meijers et al, 2010). However, an oral preparation of lactic acid bacteria did not reduce serum p-cresol concentrations in hemodialysis patients (Hida et al, 1996). Interestingly, the results of our preliminary study showed that synbiotics may be beneficial for decreased bacterial overgrowth and normal motility patterns in patients undergoing peritoneal dialysis and hemodialysis.…”
Section: Probiotics Prebiotics and Synbioticssupporting
confidence: 56%
“…The same authors also demonstrated that oligo-fructose-inulin significantly reduced p-cresyl sulfate generation rates and serum concentrations in hemodialysis patients (Meijers et al, 2010). However, an oral preparation of lactic acid bacteria did not reduce serum p-cresol concentrations in hemodialysis patients (Hida et al, 1996). Interestingly, the results of our preliminary study showed that synbiotics may be beneficial for decreased bacterial overgrowth and normal motility patterns in patients undergoing peritoneal dialysis and hemodialysis.…”
Section: Probiotics Prebiotics and Synbioticssupporting
confidence: 56%
“…Residual renal function contributes little to total solute removal of protein-bound uremic retention solutes in HD patients (10). In this study, indoxyl sulfate and biotic-resistant lactic acid bacteria) reduced serum concentrations of indoxyl sulfate but not of p-cresyl sulfate in HD patients (27). Vice versa, we recently observed that intake of the prebiotic oligofructose-enriched inulin significantly reduced p-cresol generation and p-cresyl sulfate serum concentrations, whereas indoxyl sulfate serum concentrations were not systematically reduced, nor was the indole generation rate (clinicaltrials.gov NCT00695513) (28).…”
Section: Discussionmentioning
confidence: 60%
“…with inulin (18). Furthermore, Hida et al (31) have previously reported that a probiotic-containing Bifidobacterium infantis, Lactobacillus acidophilus, and Enterococcus faecalis decreased serum IS after an increase in Bifidobacteriaceae and a decrease in the Enterobacteriaceae. Consequently, the ability of synbiotic formulations to reduce PCS and IS levels seems dependent on their Bifidogenic effects.…”
Section: Discussionmentioning
confidence: 96%